RANCANG BANGUN KURSI RODA ELEKTRIK BERBASIS INTERNET OF THINGS (IOT) - Chrissando Mayort Sailana; Tan Suryani Sollu; Alamsyah Alamsyah (Foristek, 2021)
Wheelchairs are mobility devices that are often used by people who have difficulty walking on their feet, due to illness, injury, or disability. Most of the wheelchairs that exist today are still using the manual system. Ideally, a wheelchair is needed so that users feel free and comfortable in adjusting the wheelchair movement according to their wishes. This study aims to make an innovation in the form of designing an electric wheelchair based on the internet of things (IoT). In this tool, there are several integrated electronic components such as NodeMCU, voltage sensor that is connected to the android smartphone application. Delphi XE8 software functions to create control applications that can be controlled via a smartphone. The control system on a smartphone uses an internet connection to process the wheelchair control system. This tool is very dependent on the connection and stability of the internet network. Design of electric wheelchair based IoT, has the performance that a wheelchair can carry a maximum load of 30kg at a speed of 0.79m / second, plus an accumulator / battery load and a 6.4kg DC motor, so that the total load can be under of 36.4kg.